2019
DOI: 10.1002/mgg3.720
|View full text |Cite
|
Sign up to set email alerts
|

Identifying gene mutations of Chinese patients with polycystic kidney disease through targeted next‐generation sequencing technology

Abstract: Background Polycystic kidney disease (PKD) is the most common hereditary kidney disease. The main mutational genes causing autosomal dominant polycystic kidney disease (ADPKD) are PKD1 and PKD2 as well as some rare pathogenic genes. Unilateral PKD is rare in clinics, and its association with gene mutations is unclear. Methods Targeted next‐generation sequencing (NGS) was performed to detect the renal ciliopathy‐associated genes (targeted NGS panel including 63 genes) in PKD patients. Results Forty‐eight PKD1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Sen et al reported the results of analysis of an SRNS‐targeted diagnostic gene panel performed for 302 patients, confirming genetic diagnoses in 26.6% of the patients 23 . Another study of 44 patients with typical PKD who underwent targeted NGS testing with 63 related genes revealed 48 related mutation sites in PKD1 and PKD2 24 …”
Section: Discussionmentioning
confidence: 93%
“…Sen et al reported the results of analysis of an SRNS‐targeted diagnostic gene panel performed for 302 patients, confirming genetic diagnoses in 26.6% of the patients 23 . Another study of 44 patients with typical PKD who underwent targeted NGS testing with 63 related genes revealed 48 related mutation sites in PKD1 and PKD2 24 …”
Section: Discussionmentioning
confidence: 93%